Design and application of novel metamaterial elements and configurations - Zhu, J (2011)
Metamaterials are artificially constructed "materials" which are formed from arrays of engineered elements. By designing individual elements as well as their interactions, the propagation of electromagnetic (EM) waves within the structure can be manipulated, so that new responses can be realised which may not be found in nature. The subject of this research concerns the study of miniaturised elements with strong EM responses so that the constructed metamaterial can better approximate an ordinary low-loss material. The research involves designing miniaturised magnetic resonators operating in the microwave frequency range. A novel resonator prototypes, so-called “helical resonators”, have been successfully designed and fabricated whose physical sizes can fall below 1% of the free space wavelength at resonance. This contributes to a size reduction of 90% compared with previously published work. In addition, an analytical model has been developed, so that the resonance parameters of a helical resonator have explicit expressions. In particular, a constant optimal metallic fill ratio is demonstrated to exist, which can achieve a minimum resonant frequency and a maximum miniaturisation for any given outmost dimension of the element. The accuracy of the model has been verified by both simulation and experiment. The frequency responses of fabricated helical elements were measured using a vector network analyser and a pair of small loop non- resonant dipole probes, and the parameters were extracted using the phase frequency fit method which proves to have the best accuracy and robustness. The properties of a regular square array of helical resonators are subsequently investigated, which can be regarded as a two-dimensional metamaterial. A relevant analytical model has been developed, which characterises the array as an equivalent sheet with surface current distributions, rather than an artificial medium with finite thickness. The relation between the macroscopic EM fields and the small scale properties of individual helical resonators are then established. In particular, the helical resonators are observed to be inherently chiral, thus the assembled interlocking array exhibits dichroism. The transmission coefficients for the circular EM waves with two different polarisation states have been derived, which have been verified by simulation and measurement results as well. In addition, it has been theoretically demonstrated that the resonator elements and their spacings can be engineered, so that the circular EM wave with one particular polarisation state can be totally attenuated around the element resonance, while the other state suffers negligible attenuation. A quadratic relation between the optimal array spacing and the elements’ quality factor has been demonstrated.